2D QSAR studies of the inhibitory activity of a series of substituted purine derivatives against c-Src tyrosine kinase. Issue 4 (1st October 2016) - Sharma, Mukesh C.
Abstract: A series of 34 substituted purine analogues derivatives were subjected to quantitative structure-activity relationship analyses as inhibitors of c-Src tyrosine kinase. Partial least squares regression was applied to derive QSAR models, which were further validated for statistical significance by internal and external validation. The best QSAR model developed had a good predictive correlation coefficient ( r 2 ) of 0.8319, a significant cross-validated correlation coefficient ( q 2 ) of 0.7550, and an r 2 for the external test set (pred_r 2 ) of 0.7983. It was developed from the PLS method with descriptors including the SsCH3 E-index, H-Donor Count, T_2_Cl_3, and negative correlation with SsOHcount. The current study provides better insight into the future design of more potent c-Src tyrosine kinase inhibitors prior to synthesis.